Molecular Targets for Novel Therapeutics in Pediatric Fusion-Positive Non-CNS Solid Tumors - Chang, Wen-I; Lin, Claire; Liguori, Nicholas; Honeyman, Joshua N.; DeNardo, Bradley; El-Deiry, Wafik (Frontiers in Pharmacology, 2022)
Chromosomal fusions encoding novel molecular drivers have been identified in several solid tumors, and in recent years the identification of such pathogenetic events in tumor specimens has become clinically actionable. Pediatric sarcomas and other rare tumors that occur in children as well as adults are a group of heterogeneous tumors often with driver gene fusions for which some therapeutics have already been developed and approved, and others where there is opportunity for progress and innovation to impact on patient outcomes. We review the chromosomal rearrangements that represent oncogenic events in pediatric solid tumors outside of the central nervous system (CNS), such as Ewing Sarcoma, Rhabdomyosarcoma, Fibrolamellar Hepatocellular Carcinoma, and Renal Cell Carcinoma, among others. Various therapeutics such as CDK4/6, FGFR, ALK, VEGF, EGFR, PDGFR, NTRK, PARP, mTOR, BRAF, IGF1R, HDAC inhibitors are being explored among other novel therapeutic strategies such as ONC201/TIC10.